Computationally driven discovery of SARS-CoV-2 Mpro inhibitors: from design to experimental validation. Issue 13 (7th March 2022) - El Khoury, Léa; Jing, Zhifeng; Cuzzolin, Alberto; Deplano, Alessandro; Loco, Daniele; Sattarov, Boris; Hédin, Florent; Wendeborn, Sebastian; Ho, Chris; El Ahdab, Dina; Jaffrelot Inizan, Theo; Sturlese, Mattia; et al.
Abstract : The dominant binding mode of the QUB-00006-Int-07 main protease inhibitor during absolute binding free energy simulations. Abstract : We report a fast-track computationally driven discovery of new SARS-CoV-2 main protease (M pro ) inhibitors whose potency ranges from mM for the initial non-covalent ligands to sub-μM for the final covalent compound (IC50 = 830 ± 50 nM). The project extensively relied on high-resolution all-atom molecular dynamics simulations and absolute binding free energy calculations performed using the polarizable AMOEBA force field. The study is complemented by extensive adaptive sampling simulations that are used to rationalize the different ligand binding poses through the explicit reconstruction of the ligand–protein conformation space. Machine learning predictions are also performed to predict selected compound properties. While simulations extensively use high performance computing to strongly reduce the time-to-solution, they were systematically coupled to nuclear magnetic resonance experiments to drive synthesis and for in vitro characterization of compounds. Such a study highlights the power of in silico strategies that rely on structure-based approaches for drug design and allows the protein conformational multiplicity problem to be addressed. The proposed fluorinated tetrahydroquinolines open routes for further optimization of M pro inhibitors towards low nM affinities.